2018
DOI: 10.4236/ojss.2018.89019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Deforestation on the Quality of Drainage Water in the &#381elezná Model Area

Abstract: The article is focused on the changes in soil characteristics caused by the drainage of agricultural soils in the Czech Republic. The basis of the research was to compare current state with the state before drainage using available historical data. To resolve the subject of the research, two smaller study areas with different soil uses were chosen. The Haklovy Dvory area is an arable land that is intensively used. The other area is used mainly for grazing (extensively) and it is called Železná study area. In m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This station was placed close to the soil profile which was excavated in the drained meadow. The soil profile in the drained meadow was also close to sampling point K3/D where Vopravil at al. (2018) collected the drainage water samples in the previous years.…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…This station was placed close to the soil profile which was excavated in the drained meadow. The soil profile in the drained meadow was also close to sampling point K3/D where Vopravil at al. (2018) collected the drainage water samples in the previous years.…”
Section: Methodssupporting
confidence: 65%
“…The drainage lines were placed at a depth of 1 m (Vopravil et al 2008) and the system is still functional. According to Vopravil et al (2008), the spacing of drains is between 7.5 and 11 m. In this locality, Vopravil et al (2018) collected drainage water samples (plus stream and underground water samples) and measured different chemical indicators in these samples. Vopravil et al (2008) reported that the drainage water collected in the locality was not polluted and its flow rate was relatively low.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation